A retrospective safety and efficacy analysis of the first patients treated with eribulin for metastatic breast cancer in Stockholm, Sweden. (April 2015) - Kessler, Luisa; Falato, Claudette; Margolin, Sara; Bergh, Jonas; Foukakis, Theodoros
Abstract: Backgrounds. Eribulin is a non-taxane, microtubule dynamics inhibitor approved for the treatment of patients with metastatic breast cancer (MBC) in Europe in March 2011. Material and methods. For the purpose of an internal quality control, all patients with MBC treated with eribulin at Karolinska University Hospital were registered in a database. Clinical data were collected retrospectively for patients that were registered by August 2012 and safety and efficacy of eribulin were evaluated. Treatment toxicity including fatigue, neurotoxicity and infection was graded according to CTCAE v4.0. Objective response to treatment was investigated using routinely performed radiological assessments. When only clinical assessments were made, the evaluation of the treating physician was used. Furthermore, the efficacy of eribulin was investigated in different tumor subtypes. Results. Forty-eight patients who received at least one cycle of eribulin were identified. Most patients were heavily pretreated with a median of 3 (range 1–7) previous chemotherapy lines prior to eribulin. Median patient age was 56 years (range 35–74). At the end of the analysis, 23 patients were alive and two were still treated with eribulin. No hypersensitivity reactions and no toxic deaths were seen. Fatigue grade 3–4 was observed in three patients (6.3%). One patient experienced grade 4 neurotoxicity. Grade 3–4 neutropenia was documented in 18.8%, and three patients were treated for a grade 3 infection. Interestingly, three individuals developed Herpes zoster reactivation. One patient responded to treatment with complete remission, while 33.3% had a partial response. 48% of all patients had a clinical benefit (objective response or stable disease for more than six months). Conclusions. Eribulin administered outside of a clinical trial in patients with advanced breast cancer was safe and well tolerated. A clinical benefit was seen in half of the cases. No statistically significant differences in objective response or survival were observed between histopathological subgroups.